Preparation method of porous nano-beta-tricalcium phosphate

CN122977333APending Publication Date: 2026-10-27HUBEI THREE GORGES LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206232.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,现有制备方法如造孔剂法、发泡法、冷冻干燥法等,在实现纳米粉体均匀分散、孔径精确调控、孔隙高度连通以及维持足够力学强度等方面仍存在诸多不足

Benefits of technology

1.本发明采用改良溶剂热法,整体制备流程简洁清晰,原料选择范围广泛,原料易得、成本低廉、通用性极强。同时,本发明通过精准限定Ca/P摩尔比、pH值、反应温度、保温时间等核心参数,反应体系稳定可控,大幅降低了工艺调控难度,实验重复性较好,有效解决了传统工艺批次稳定性差的问题,具备良好的工业化批量生产潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977333A_ABST
    Figure CN122977333A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of biomedical ceramic powder, and particularly relates to a preparation method of porous nano beta-tricalcium phosphate (beta-TCP). A calcium source and an organic phosphorus source are respectively dissolved in an organic solvent, and stirring is performed until the solution is clear to obtain a calcium source solution and a phosphorus source solution; the phosphorus source solution is slowly added to the calcium source solution, and an organic base reagent is used to adjust the pH of the system to 7.0-10.0 while adding, and uniform precursor solution is obtained by continuous stirring; the precursor solution is transferred into a reaction kettle, and is kept at 160-220 DEG C for 10-24 h, and porous nano beta-TCP is obtained after natural cooling. The application has the advantages of simple process, fast synthesis speed, mild conditions, controllable product morphology, avoidance of introduction of inorganic impurities, overcoming of the defects of uneven particle size and easy agglomeration of samples prepared by general chemical precipitation method, and suitability for large-scale preparation in the field of biomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomaterial preparation technology, specifically relating to a method for preparing porous nano-β-TCP. Background Technology

[0002] Bone defect repair is a major challenge in orthopedic clinicians. Bone defects caused by tumor resection, trauma, and infection often fail to heal spontaneously and require treatment with bone grafts or artificial bone substitutes. While autologous bone grafting yields ideal results, its availability is limited and donor site complications exist; allogeneic bone carries risks of immune rejection and disease transmission. Therefore, developing bone repair materials that combine good biocompatibility, biodegradability, and osteogenic activity is of great significance.

[0003] β-TCP, due to its chemical composition similar to natural bone inorganic matter, excellent biocompatibility, and ability to gradually degrade in vivo and guide new bone ingrowth, has become one of the most widely used bioceramics in bone tissue engineering. Compared with hydroxyapatite, β-TCP has a more suitable degradation rate, facilitating complete replacement by newly formed bone tissue. However, dense β-TCP lacks a porous structure conducive to cell ingrowth and vascularization, limiting its bone repair efficacy. Studies have shown that an ideal bone repair scaffold should possess a three-dimensionally interconnected porous structure to promote cell adhesion, proliferation, and nutrient transport. However, the introduction of porous structures often leads to a significant decrease in mechanical properties, and the contradiction between porosity and strength is a key bottleneck restricting its clinical application.

[0004] In recent years, reducing the grain size of β-TCP to the nanoscale has significantly improved the specific surface area and surface activity of materials, which is beneficial for protein adsorption and cellular response, thereby accelerating bone healing. However, existing preparation methods, such as pore-forming agent methods, foaming methods, and freeze-drying methods, still have many shortcomings in achieving uniform dispersion of nanoparticles, precise control of pore size, high pore connectivity, and maintaining sufficient mechanical strength. Therefore, developing a simple, structurally controllable, and high-performance porous nano-β-TCP preparation method has significant clinical value and industrialization prospects. Summary of the Invention

[0005] This invention aims to overcome the shortcomings of existing technologies and provide a method for preparing porous nano-β-TCP. This method uses a solvothermal approach to prepare porous nano-β-TCP.

[0006] This method is simple and reproducible, and the resulting porous nano-β-TCP has a uniform and controllable three-dimensional pore structure, high specific surface area and good mechanical properties, making it suitable for bone defect repair and bone tissue engineering scaffold applications.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing porous nano-β-TCP includes the following steps: (1) Dissolve the calcium source and the organophosphorus source in an organic solvent respectively, and stir until clear to obtain a calcium source solution and a phosphorus source solution; (2) Slowly add the phosphorus source solution to the calcium source solution, while adjusting the pH of the system to 7.0~10.0 with an organic base reagent, and continue stirring to obtain a homogeneous precursor solution; (3) The precursor solution was transferred into the reactor and kept at 160~220℃ for 10~24 h. After natural cooling, porous nano β-TCP was obtained.

[0008] The calcium source mentioned in step (1) includes one or more of calcium chloride, calcium iodide, calcium bromide, calcium acetylacetone, calcium hydroxide, calcium carbonate, calcium oxide, and calcium acetate.

[0009] The phosphorus source mentioned in step (1) includes one or more of trimethyl phosphate, triethyl phosphate, triphenylphosphine, and phenylphosphonic acid.

[0010] The organic solvent mentioned in step (1) includes one or more of methanol, ethanol, ethylene glycol, propylene glycol, isopropanol, acetone, N,N-dimethylformamide, dimethyl sulfoxide, 1,2,3-hexanetriol, and 2-methyl-1,3-propanediol.

[0011] The organic solvent is an anhydrous solvent. An anhydrous environment refers to a water content as close to 0 as possible, which is understood by those skilled in the art to be below 0.01%. The advantage of this anhydrous organic solvent is that the extremely low water content of the system can inhibit the nucleation and growth of HA impurities at the source, avoiding… OH enters the product lattice, ensuring β TCP products exhibit high phase purity; they can suppress the hydrolysis side reaction of precursors upon contact with water; the calcium-phosphorus molar ratio is easily and precisely controlled; and the products demonstrate good batch stability. Furthermore, they can regulate grain growth kinetics to obtain β-type products with controllable morphology and particle size. TCP powder reduces the process pressure of subsequent high-temperature heat treatment and reduces the risk of high-temperature phase transformation.

[0012] Unless otherwise specified, all solvents used in this embodiment are anhydrous solvents.

[0013] In step (1), the molar ratio of calcium source to phosphorus source is 1-2, preferably 1.5.

[0014] Step (2) also includes adding a surfactant to the calcium source solution; The surfactants include one or more of oleylamine, oleic acid, calcium oleate, aluminum oleate, aluminum stearate, P123, F127, hexadecylamine, dodecylamine, diethanolamide of oleic acid, dioctadecyl dimethyl ammonium chloride, and fatty alcohol polyoxypropylene ether phosphate, etc., and the mass of the surfactant is 1%-10% of the total solvent mass.

[0015] The organic base reagents mentioned in step (2) include ethylamine, diethylamine, triethylamine (TEA), propylamine, isopropylamine, diisopropylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline (DMA), monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA), etc.

[0016] The solvothermal reaction temperature in step (3) is 160~220℃, the holding time is 10~24 h, and it is naturally cooled to room temperature. The high-temperature solvothermal environment can drive the burst nucleation of β-TCP and slow and controllable growth, achieving a narrow particle size distribution and target pore structure; at the same time, the system contains almost no free water and lacks the source of hydroxyl groups required for HA generation, thus inhibiting HA nucleation and precipitation; sufficient heat preservation ensures the crystallinity of β-TCP, reduces the amorphous calcium phosphate intermediate phase, and avoids the subsequent generation of HA.

[0017] After the product cools naturally in step (3), a post-processing step is also included, namely, obtaining porous nano β-TCP after centrifugation, washing and drying.

[0018] Centrifugal separation, with the rotation speed controlled at 6000-8000 rpm; Wash with anhydrous ethanol until the pH reaches 6-8; The drying method is vacuum drying, with a temperature of 50~100 ℃ and a time of 12~24h.

[0019] The present invention also provides a porous nano-β-TCP, which is prepared by the method described above. The β-TCP is porous nanoscale with a particle size of 30-220 nm, an average pore size of 10-20 nm, and an HA content of <0.01%.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. This invention employs a modified solvothermal method, resulting in a simple and clear overall preparation process. It allows for a wide range of raw material selection, with readily available, low-cost, and highly versatile materials. Furthermore, by precisely controlling core parameters such as the Ca / P molar ratio, pH value, reaction temperature, and holding time, the reaction system remains stable and controllable, significantly reducing the difficulty of process control. The invention exhibits good experimental repeatability and effectively solves the problem of poor batch stability in traditional processes, demonstrating excellent potential for industrial-scale mass production.

[0021] 2. This invention, through the precise control of specific surfactant formulations, accurate pH control with organic bases, and solvothermal synergistic reactions, can accurately construct a uniform and controllable three-dimensional interconnected porous structure with well-distributed nanoscale pores and excellent channel connectivity. This structure can meet the needs of bone defect repair, providing ample space for osteoblast attachment, proliferation, and differentiation, ensuring nutrient transport and metabolic waste removal, while guiding the orderly growth of new bone tissue along the pores, significantly improving bone repair efficacy.

[0022] 3. The porous nano-β-TCP prepared in this invention possesses the dual advantages of nanoparticle size and porous structure, exhibiting an ultra-high specific surface area. This significantly increases the contact area between the material and body fluids and cells, effectively enriching growth factors and adsorbing cells, thus significantly improving the material's biocompatibility and osteoinductive activity. Simultaneously, the high specific surface area structure optimizes the material's degradation rate, precisely matching it with the growth rate of new bone tissue, avoiding the repair failure problems caused by excessively rapid or slow degradation of traditional materials.

[0023] 4. This invention employs an organic solvent system combined with a mild solvothermal reaction, eliminating high-temperature sintering and violent reactions throughout the process. This effectively avoids impurity formation and crystal defects. Combined with multiple centrifugal washing with anhydrous ethanol and vacuum drying, the final product exhibits high purity, uniform composition, and no harmful residues. The material possesses excellent overall biocompatibility, is non-toxic and non-irritating, and will not cause adverse reactions such as inflammation or rejection after implantation in the human body. It is stably degraded and can be replaced by human tissue. Attached Figure Description

[0024] Figure 1 This is a SEM image of the porous nano-β-TCP prepared in Example 1.

[0025] Figure 2 The image shows the XRD pattern of the porous nano-β-TCP prepared in Example 1.

[0026] Figure 3 The image shows the XRD pattern of the HA prepared in Comparative Example 1.

[0027] Example 1 (1) Weigh 0.024 mol of calcium chloride and dissolve it in 50 mL of a mixed solution of ethylene glycol and N,N-dimethylformamide (volume ratio 1:1). Separately, take 0.016 mol of trimethyl phosphate and dissolve it in 50 mL of a mixed solution of ethylene glycol and N,N-dimethylformamide (volume ratio 1:1). Stir each solution thoroughly. (2) Add a mixture of oleylamine and dodecylamine (mass ratio 1:1) to the calcium source solution. The mass of the surfactant is 5% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent triethanolamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 30~150 nm and a specific surface area of ​​85.50 m². 2 / g, average mesopore size is 17.81nm, HA content is 95ppm. SEM image as follows. Figure 1 As shown, the XRD pattern is as follows Figure 2 As shown.

[0028] Example 2 (1) Weigh 0.024 mol of calcium acetate and dissolve it in 50 mL of a mixed solution of methanol and N,N-dimethylformamide (volume ratio 1:1). Separately, take 0.016 mol of triethyl phosphate and dissolve it in 50 mL of a mixed solution of methanol and N,N-dimethylformamide (volume ratio 1:1). Stir each solution thoroughly. (2) Add hexadecylamine to the calcium source solution. The mass of the surfactant is 3% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding the solution, use the organic base reagent triethylamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 180°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 7000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 50°C for 24 h to obtain porous nano-β-TCP with a particle size range of 50~220 nm and a specific surface area of ​​79.21 m². 2 / g, with an average mesopore size of 18.63nm and an HA content of 82ppm.

[0029] Example 3 (1) Weigh 0.024 mol of calcium iodide and dissolve it in 50 mL of a mixed solution of isopropanol and dimethyl sulfoxide (volume ratio 1:1). Separately, weigh 0.016 mol of triphenylphosphine and dissolve it in 50 mL of a mixed solution of isopropanol and dimethyl sulfoxide (volume ratio 1:1). Stir each solution thoroughly. (2) Add P123 to the calcium source solution. The mass of the surfactant is 1% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent ethylamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 160°C for 24 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 6000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 100℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 60~210 nm and a specific surface area of ​​76.45 m². 2 / g, with an average mesopore size of 18.11nm and an HA content of 77ppm.

[0030] Example 4 (1) Weigh 0.024 mol of calcium bromide and dissolve it in 50 mL of a mixed solution of ethanol and N,N-dimethylformamide (volume ratio 1:1). Separately, take 0.016 mol of trimethyl phosphate and dissolve it in 50 mL of a mixed solution of ethanol and N,N-dimethylformamide (volume ratio 1:1). Stir each solution thoroughly. (2) Add F127 to the calcium source solution. The mass of the surfactant is 5% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent diethylamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 220°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 7000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 30~130 nm and a specific surface area of ​​96.83 m². 2 / g, with an average mesopore size of 15.31nm and an HA content of 98ppm.

[0031] Example 5 (1) Weigh 0.024 mol of calcium hydroxide and dissolve it in 50 mL of a mixed solution of ethanol and N,N-dimethylformamide (volume ratio 1:1). Separately, take 0.016 mol of phenylphosphonic acid and dissolve it in 50 mL of a mixed solution of ethanol and N,N-dimethylformamide (volume ratio 1:1). Stir each solution thoroughly. (2) Add oleic acid and oleic acid diethanolamide (mass ratio 1:1) to the calcium source solution. The mass of the surfactant is 10% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent diethanolamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 100℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 60~200 nm and a specific surface area of ​​78.34 m². 2 / g, with an average mesopore size of 18.52nm and an HA content of 69ppm.

[0032] Example 6 (1) Weigh 0.024 mol calcium acetylacetonate and dissolve it in 50 mL of a mixed solution of acetone and dimethyl sulfoxide (volume ratio 1:1). Separately, take 0.016 mol trimethyl phosphate and dissolve it in 50 mL of a mixed solution of acetone and dimethyl sulfoxide (volume ratio 1:1). Stir each solution thoroughly. (2) Add dioctadecyl dimethyl ammonium chloride to the calcium source solution. The mass of the surfactant is 3% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding the solution, use the organic base reagent propylamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 30~170 nm and a specific surface area of ​​89.51 m². 2 / g, with an average mesopore size of 16.81nm and an HA content of 84ppm.

[0033] Example 7 (1) Weigh 0.024 mol of calcium chloride and dissolve it in 50 mL of a mixed solution of propylene glycol and N,N-dimethylformamide (volume ratio 1:1). Separately, take 0.016 mol of triethyl phosphate and dissolve it in 50 mL of a mixed solution of propylene glycol and N,N-dimethylformamide (volume ratio 1:1). Stir each solution thoroughly. (2) Add F127 to the calcium source solution. The mass of the surfactant is 3% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent isopropylamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 50~180 nm and a specific surface area of ​​80.98 m². 2 / g, with an average mesopore size of 16.12nm and an HA content of 89ppm.

[0034] Example 8 (1) Weigh 0.024 mol calcium acetylacetonate and dissolve it in 50 mL N,N dimethylformamide, and separately dissolve 0.016 mol triphenylphosphine in 50 mL N,N dimethylformamide, and stir them evenly. (2) Add fatty alcohol polyoxypropylene ether phosphate to the calcium source solution. The mass of the surfactant is 2% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent diisopropylamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-β-TCP with a particle size range of 40~160 nm and a specific surface area of ​​96.31 m². 2 / g, with an average mesopore size of 15.23nm and an HA content of 62ppm.

[0035] Comparative Example 1 (1) Weigh 0.024 mol of calcium chloride and dissolve it in 50 mL of a mixed solution of ethylene glycol and N,N-dimethylformamide (volume ratio 1:1). Separately, weigh 0.016 mol of ammonium dihydrogen phosphate and dissolve it in 50 mL of a mixed solution of ethylene glycol and water (volume ratio 1:1). Stir each solution thoroughly. (2) Add a mixture of oleylamine and dodecylamine (mass ratio 1:1) to the calcium source solution. The mass of the surfactant is 5% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent triethanolamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-HA with a particle size range of 200~250 nm and a specific surface area of ​​56.32 m². 2 / g, with an average mesopore size of 21.52nm. XRD pattern as shown below. Figure 3 As shown.

[0036] Comparative Example 2 (1) Weigh 0.024 mol of calcium chloride and dissolve it in 50 mL of a mixed solution of ethylene glycol and N,N-dimethylformamide. Separately, weigh 0.016 mol of trimethyl phosphate and dissolve it in 50 mL of a mixed solution of ethylene glycol and water (volume ratio 1:1). Stir each solution thoroughly. (2) Add a mixture of oleylamine and dodecylamine (mass ratio 1:1) to the calcium source solution. The mass of the surfactant is 5% of the total solvent mass. Slowly add the phosphorus source solution to the calcium source solution. While adding, use the organic base reagent triethanolamine to adjust the pH of the system to 7.0~10.0. Continue stirring to obtain a homogeneous precursor solution. (3) Transfer the precursor solution into the reactor and keep it at 200°C for 12 h. After the heat preservation is completed, let it cool naturally to room temperature. (4) The precipitate was separated by centrifugation at 8000 rpm. The solution was washed with anhydrous ethanol until neutral. The precipitate was then vacuum dried at 80℃ for 12 h to obtain porous nano-HA with a particle size range of 180~240 nm and a specific surface area of ​​60.79 m². 2 / g, with an average mesopore diameter of 20.84nm.

Claims

1. A method for preparing porous nano-β-TCP, characterized in that, Includes the following steps: (1) Dissolve the calcium source and the organophosphorus source in an organic solvent respectively, and stir until clear to obtain a calcium source solution and a phosphorus source solution; (2) Slowly add the phosphorus source solution to the calcium source solution, while adjusting the pH of the system to 7.0~10.0 with an organic base reagent, and continue stirring to obtain a homogeneous precursor solution; (3) The precursor solution was transferred into the reactor and kept at 160~220℃ for 10~24 h. After natural cooling, porous nano β-TCP was obtained.

2. The method for preparing porous nano-β-TCP according to claim 1, characterized in that, The calcium source mentioned in step (1) includes one or more of calcium chloride, calcium iodide, calcium bromide, calcium acetylacetone, calcium hydroxide, calcium carbonate, calcium oxide, and calcium acetate. The phosphorus source includes one or more of trimethyl phosphate, triethyl phosphate, triphenylphosphine, and phenylphosphonic acid; The organic solvents include one or more of methanol, ethanol, ethylene glycol, propylene glycol, isopropanol, acetone, N,N-dimethylformamide, dimethyl sulfoxide, 1,2,3-hexanetriol, and 2-methyl-1,3-propanediol; The organic solvent is an anhydrous solvent.

3. The method for preparing porous nano-β-TCP according to claim 1, characterized in that, The molar ratio of calcium source to phosphorus source in step (1) is 1-2, preferably 1.

5.

4. The method for preparing porous nano-β-TCP according to claim 1, characterized in that, Step (2) also includes adding a surfactant to the calcium source solution; Surfactants include one or more of the following: oleylamine, oleic acid, calcium oleate, aluminum oleate, aluminum stearate, P123, F127, hexadecylamine, dodecylamine, diethanolamide of oleic acid, dioctadecyl dimethyl ammonium chloride, and fatty alcohol polyoxypropylene ether phosphate.

5. The method for preparing porous nano-β-TCP according to claim 4, characterized in that, The mass of the surfactant is 1%-10% of the total solvent mass.

6. The method for preparing porous nano-β-TCP according to claim 1, characterized in that, The organic base reagent used in step (2) includes any one or more combinations of ethylamine, diethylamine, triethylamine, propylamine, isopropylamine, diisopropylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline, monoethanolamine, diethanolamine, and triethanolamine.

7. The method for preparing porous nano-β-TCP according to claim 1, characterized in that, The solvothermal reaction temperature in step (3) is 160~220 ℃, the holding time is 10~24 h, and it is naturally cooled to room temperature.

8. The method for preparing porous nano-β-TCP according to claim 1, characterized in that, After the product cools naturally in step (3), a post-processing step is also included, namely, obtaining porous nano β-TCP after centrifugation, washing and drying.

9. The method for preparing porous nano-β-TCP according to claim 8, characterized in that, Centrifugal separation, with the rotation speed controlled at 6000-8000 rpm; Wash with anhydrous ethanol until the pH reaches 6-8; The drying method is vacuum drying, with a temperature of 50~100 ℃ and a time of 12~24h.

10. A porous nano-β-TCP prepared according to the method described in claims 1-9, characterized in that, The β-TCP is porous nanoscale with a particle size of 30-220 nm, an average pore size of 10-20 nm, and a hydroxyapatite (HA) content of <0.01%.